The first thing you have to do is group together like terms, and remember that since this is an equation, what you do to one side you have to do to the other side. I'll show you this in steps.
4x + 2x = 9x - 6 Group together like-terms on the left hand side to get
6x = 9x - 6 Subtract 9x from both sides to get
6x - 9x = -6 (at this point, note that the 9x on the right hand side disappeared. This should happen, since subtract 9x would make 9x on the right hand side equal to zero).
Now, group together like terms on the left hand side, to get
-3x = -6
Since our goal is to isolate x, we divide both sides by -3
-3x/-3 = -6/-3
x = 2
2006-11-28 16:37:07
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
4x+2x=9x-6
=> 6x=9x-6
=> 9x-6x=6
=> 3x=6
=> x=2
hence x=2
2006-11-29 00:36:56
·
answer #2
·
answered by Vikram M 2
·
0⤊
0⤋
4x+2x=6x,you need to get x by itself so subtract 9x from both sides. -3x= -6 now divide by -3 the answer is 2
2006-11-29 00:38:00
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
4x+2x=9x-6 subtract 9x from each side.
-3x=-6 divide by -3
x=2
2006-11-29 02:05:10
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
4x + 2x = 9x - 6
6x = 9x - 6 add 4x and 2x together
-3x = -6 subbtract 9x to both side, 6x - 9x = -3x
x = 2 divide both side by -2
x is 2
2006-11-29 00:51:33
·
answer #5
·
answered by Thrive 1
·
0⤊
0⤋
add 4x+2x together = 6X
then subtract the 9x to the other side and get -3x=-6
x=2
2006-11-29 00:35:49
·
answer #6
·
answered by gigi 2
·
0⤊
0⤋
4x + 2x = 9x -6
6x - 9x = -6
-3x = -6
3x = 6
x = 6/3
x = 2
2006-11-29 00:40:57
·
answer #7
·
answered by Nikolas S 6
·
0⤊
0⤋
4x+2x=9x-6
6x=9x-6
-3x=-6
x=2
2006-11-29 00:36:10
·
answer #8
·
answered by you 2
·
0⤊
0⤋
6X=9X-6 (add the 2X and 4X)
-3X=-6 (subtract 9X from both sides)
3X=6 (multiply both sides by -1)
X=2 (devide both sides by 3)
2006-11-29 00:38:13
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
4x + 2x = 9x - 6
6x - 9x = -6
-3x = -6
3x = 6
x = 2
2006-11-29 00:37:34
·
answer #10
·
answered by Srinivas c 2
·
0⤊
0⤋